IMMUNOMODULATORY THERAPIES FOR PREVENTING THROMBOSIS IN IMMUNE-MEDIATED MICROVASCULAR THROMBOTIC DISEASES (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Immune-mediated microvascular thrombotic diseases (IMTD), such as systemic lupus erythematosus (SLE) and antiphospholipid syndrome (APS), increase the risk of microvascular thrombosis due to chronic inflammation and autoimmune activity. While anticoagulant therapy is crucial for managing thrombotic events, immunomodulatory therapies may provide additional benefits by targeting underlying immune dysfunction. This study evaluated the efficacy of biologic agents (IL-6 antagonists, TNF inhibitors, rituximab) and complement inhibitors in reducing thrombotic risk over 12 months in 50 patients with IMTD (aged 18–65). Inflammatory markers (CRP, IL-6) and thrombotic indicators (D-dimer, fibrinogen) were elevated at baseline and significantly decreased post-therapy (p